Atmospheric Photopolymerization of Acrylamide Enabled by Aqueous Glycerol Mixtures: Characterization and Application for Surface‐Based Microfluidics. Issue 10 (20th July 2017) - Gleichmann, Tobias; Rostas, Arpad; Wörner, Jakob; Schleicher, Erik; Gutzweiler, Ludwig; Hamouda, Boris; Zengerle, Roland; Koltay, Peter; Riegger, Lutz
Abstract : Nanoliter volumes of aqueous acrylamide–bisacrylamide gel precursor solution including Irgacure 2959 are photopolymerized in presence of atmospheric oxygen using glycerol as an additive. Polymerization times—reduced down to 5 s—and completeness are proportional to the glycerol concentration. The findings allow for the fabrication of microfluidic hydrogel structures by printing the solution followed by selective UV exposure. Abstract : Polyacrylamide usually is the material of choice for electrophoretic separation in slab gels, capillaries, and microfluidic devices. So far its polymerization requires anaerobic environments because oxygen impurities inhibit or even terminate the polymerization reaction of acrylamide. Here, it is demonstrated that gel precursor solutions with glycerol contents above 20 vol% enable direct atmospheric photopolymerization of acrylamide with no need for sealing or degassing the solution in advance. The positive effect of glycerol on the polymerization reaction is proven by simulation‐validated electron paramagnetic resonance measurements. Nuclear magnetic resonance reveals that glycerol does not interfere with the reaction indicating that the observed enhancement in polymerization is owed to the low oxygen solubility of aqueous glycerol mixtures. Glycerol concentrations of >60 vol% in the gel precursor solution enable complete polymerization of volumes down to 5 nL within less than 5 s. This enables using liquid handling robots to fabricate channel‐free open microfluidic structures of solid polyacrylamide hydrogel in a low‐cost automated manner in a standard lab environment.